1999
DOI: 10.1097/00001756-199907130-00024
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potentials reveal covert distractibility in closed head injuries

Abstract: Event-related brain potentials (ERPs) to auditory stimuli were recorded from 11 closed head injured (CHI) and 10 age-matched healthy adults. Auditory stimuli consisted of sequences of repetitive standard tones (600 Hz), occasionally replaced by deviant tones (660 Hz) or by natural novel sounds. Subjects were instructed to ignore auditory stimuli while concentrating on a demanding visuo-motor tracking task. CHI patients showed, in comparison to control subjects, significantly enhanced late P3a component in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 5 publications
1
27
1
2
Order By: Relevance
“…Other recent studies have reported findings of increased orienting P300 amplitude responses to both novel (Solbakk, Reinvang, Nielsen, & Sundet, 1999) and emotional (Kaipio et al, 1999) stimuli following head trauma. These observations are consistent with our findings.…”
Section: H a B I T U A T I O N A T P Zmentioning
confidence: 77%
“…Other recent studies have reported findings of increased orienting P300 amplitude responses to both novel (Solbakk, Reinvang, Nielsen, & Sundet, 1999) and emotional (Kaipio et al, 1999) stimuli following head trauma. These observations are consistent with our findings.…”
Section: H a B I T U A T I O N A T P Zmentioning
confidence: 77%
“…In a study of patients with closed-head injuries, Kaipio et al [1999] reported MMNs to deviant tones similar to those in control subjects but an enhanced late subcomponent of P 3a to novel sounds, suggesting a 'normal' activation of the change detector mechanism associated with MMN but a stronger attention-switching response to large changes in the unattended acoustic environment. Consistently with this, Polo et al [1998] reported similar MMNs but enhanced P 3a responses to deviant tones in a group of chronic abstinent alcoholics.…”
Section: Use Of Erps In Clinical Research Of Involuntary Attention Anmentioning
confidence: 92%
“…Others (Heinze et al, 1992), however, including those in which it was quantified in the difference wave- Table 4 Closed head-injury effects on visual ERPs Sangal and Sangal (1996) Sangal and Sangal (1996) Polo et al (2002) Entries reflect comparisons between head-injury survivors and healthy controls. Kaipio et al (1999) Clark et al (1992) Packard and Ham (1996) Curry (1980 Keren et al (1998 Potter and Barrett (1999) Packard and Ham (1996) forms (Duncan et al, , 2005, have found significant reductions in visual N200 amplitude. Of the long latency components, P300 has been the most studied in investigations of head-injury survivors (Campbell and de Lugt, 1995).…”
Section: Amplitudementioning
confidence: 98%